Flash Eurobarometer 426 (Small and Medium Enterprises, Resource Efficiency and Green Markets, wave 3) - European Commission, Brussels DG Communication COMM A1 ´Strategy, Corporate Communication Actions and Eurobarometer´ Unit (2016)
Small and medium enterprises, resource efficiency, and green markets. Topics: actions undertaken to improve resource efficiency: saving water, saving energy, using predominantly renewable energy, saving materials, minimizing waste, selling of scrap material, recycling, designing products easy to maintain, repair, or reuse; actions to be implemented in the next two years; main reasons for undertaking actions for more resource efficiency; impact of actions on production costs over the past two years; average investment per year on resource efficiency actions over the past two years; satisfaction with return on investment made on resource efficiency; activities of the company regarding public procurement contracts that included environmental requirements; difficulties experienced; reasons for not applying; most important difficulty experienced: costs, technical tests, too much paperwork; most important support regarding efforts on resource efficiency: own financial resources, own technical expertise, external support; type of external support; difficulties encountered when trying to set up resource efficiency actions: complexity of administrative or legal procedures, difficulty to adapt environmental legislation to own company, technical requirements of legislation not up to date, choosing right resource efficiency actions for own company, cost of environmental actions, lack of environmental expertise, lack of supply of required materials, lack of demand for resource efficient products or services; most helpful measures to improve resource efficiency; green products or services offered by company; percentage of the company’s turnover in the last fiscal year coming from green products or services; time when company started selling green products or services; main markets for green products or services in the last two years; types of support for the production of green products or services: own financial resources, own technical expertise, external support; types of external support for the production of green ...